Analysis of Public Hospital Managers' Intentions in The Use of Balanced Scorecards - Tegar Fadeli Arrahma; Heru Kurnianto Tjahjono (Humanistic Network for Science and Technology (HNST), 2022)
Background: Regional public hospital has long been a ‘Badan Layanan Umum Daerah’ (BLUD) system. In BLUD system financial performance and non-financial performance must be reported once a year. The Performance report based on The Balanced Scorecard (BSC). In practice, many hospitals have not or are late in using the BSC. The purpose of this study was to assess managers' intentions in using the BSC. By using the Theory of Planned Behavior (TPB) to measure whether the determinants of behavioral attitudes, subjective norms, and control behavior are predictors of intention to use the BSC. Methods: This study used mix method sequential expalantory, a combining of a quantitative and qualitative approach with a cross-sectional design. The quantitative approach using questionnaire to measure 4 variables and then qualitative approach by document review and Focus Group Discussion (FGD) to get more comprehensive data broadly and in depth the variables. The influence of behavioral attitudes, subjective norms, and control behavior on manager intentions was analyzed by multiple linear regression. Results: Out of 67 respondents, the general intention was moderate (73%), low (15%), and high (12%). The results of the T-test showed an attitude significance of 0.205; subjective norm 0.001; behavioral control 0.004. The F test showed a p-value of 0.000. The coefficient of determination showed the effect of the three variables on the intention of 67.4%. Conclusion: The three variables simultaneously affect the intention, but partially only the subjective norm and behavioral control variables have a significant influence on the intentions of the managers.Keywords: Theory of Planned Behavior; intention; manager; Balanced Scorecard